Peran Hardiness sebagai Moderator dalam Pengaruh Job Insecurity terhadap Job Stress - Fridayanti Fridayanti; Ayu Permatasari; Adang Hambali (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to examine the role of hardiness in moderating the effect of job insecurity on job stress. The research method used is quantitative causality. The sampling technique used was simple random sampling. The total respondents in this study were 142 honorary teachers at public elementary schools in Cileunyi District, Bandung Regency. The data collection technique used a questionnaire consisting of three measuring scales, namely The Job Insecurity scale, The Job Stress Scale (JSS), and The Occupational Hardiness Questionnaire (OHQ). The data analysis technique uses the MRA (Moderated Regression Analysis) test. The results showed that job insecurity had a significant effect on job stress and hardiness could not moderate the effect of job insecurity on job stress. This shows that hardiness does not significantly affect in reducing the effect in the relation of job insecurity toward job stress.